Elite coaches have a similar prevalence of depressive symptoms to the general population and lower rates than elite athletes - Kim, S. S. Y.; Hamiliton, B.; Beable, S.; Cavadino, A.; Fulcher, M. L. (BMJ Open Sport & Exercise Medicine, 2020)
Objective The primary aim of this study was to estimate the prevalence of depressive symptoms and life stress in elite coaches. The secondary aim was to explore the associations of depressive symptoms and life stress with demographic and lifestyle variables.